Effects of a physical education intervention on children's physical activity and fitness: the PROFIT pilot study - Luiza Naujorks Reis; Cézane Priscila Reuter; Ryan Donald Burns; Clarice Maria de Lucena Martins; Jorge Mota; Adroaldo Cezar Araujo Gaya; João Francisco de Castro Silveira; Anelise Reis Gaya (BMC, 2024)
Abstract Background Physical education classes are widely accepted as one of the most effective settings for promoting physical activity and health and have often been used to implement physical activity interventions. The aim of this pilot study was to test a physical education intervention program on physical activity levels and physical fitness in a sample of school-age children. Methods Participants were a convenience sample of 50 children (34 experimental group and 16 in the comparative group) aged between 6 and 11 years old (Mean = 8.28 years). A 21-week intervention was implemented, consisting of high-intensity and physical fitness-focused exercises, in addition to a once-a-month extra class nutritional education. The following variables were evaluated before and post-intervention: physical fitness, sedentary behavior (SB), light physical activity (LPA), moderate physical activity (MVA), and vigorous physical activity (VPA). Propensity score analyses calculated the average treatment effect on the treated (ATET) within a quasi-experimental framework. Results Physical fitness variables showed improvements after the intervention, specifically for agility (ATET = -0.67 s; p < 0.001), cardiorespiratory fitness (ATET = 89.27 m; p = 0.045), lower limbs power (ATET = 4.47 centimeters; p = 0.025), and speed (ATET = -1.06 s; p < 0.001). For physical activity and SB levels, there were no improvements after intervention implementation. Conclusion The intervention program showed preliminary effectiveness to improve physical fitness of children, but not SB nor physical activity.